The Paleontological Heritage of Northern Tocantins State and Southwest Maranhão State, Brazil: a Preliminary Synthesis: UMA SÍNTESE (Terr@ Plural, 2021)
This paper aims to present a preliminary synthesis of the Paleontological Heritage of northern Tocantins State and southwest Maranhão State. It is a compound mainly from Paleozoic and Mesozoic rocks of the intracratonic Parnaíba Basin. Fossils from these regions include body fossils of sharks, gymnosperm trunks, mineralized ferns, ichnofossils of sauropods and theropods, and indeterminate leaf molds.
Keywords: Parnaíba basin; fossiliferous survey; Geoconservation; Geodiversity